Energy and Exergy Analysis of Dual Channel Solar Air Collector with Perforating “V” Corrugated Absorber Plate - Shbailat, Suhaib J.; Jassim, Najim A. (Basrah Journal for Engineering Sciences, 2018)
In This paper, an experimental study was carried out on a dual channel with perforating “V” corrugated absorber plate of solar air collector which the air flows both in upper channel and lower channel of the absorber plate for increasing heat transfer coefficient and improving thermal performance. The results of experimental procedures for dual channel with perforating “V” corrugated absorber plate of solar collector were compared with the flat plate dual channel of solar collector. Experimental calculations had been performed under Baghdad (33.34° North latitude, 44.4° East longitude) climatic conditions at different values of mass flow rates 0.021 kg/s, 0.027 kg/s and 0.32 kg/s. The results showed that the dual channel with perforating “V” corrugated absorber plate of solar collector is found to perform more efficiently than the flat plate dual channel of solar collector with increased 39% in thermal efficiency. Then, it showed that the efficiency increases with increasing mass flow rates. Also, it showed that the heat removal factor of the dual channel with perforating “V” corrugated absorber plate of solar collector is 36% more than the flat plate dual channel of solar collector. At the last part of the study, the exergy relations were derived for both collectors. The results of this part showed that the flat plate dual channel of solar collector is having largest irreversibility (exergy loss) and the dual channel with perforating “V” corrugated absorber plate of solar collector is having a greatest exergetic efficiency.